By grammar alone? : Humanism overcome and the hermeneutics of Matthias Flacius Illyricus - Koryl, Jakub (Array, 2020)
Wilhelm Dilthey once admitted that Matthias Flacius Illyricus either appropriated the fourth book of Augustine’s De Doctrina Christiana in detail or took advantage of all of the early Christian exegesis in general in his Clavis Sacrae Scripturae. The aim of this paper is partly polemical. While Flacius himself frequently proved Dilthey’s unfavorable judgment to be correct, he also followed the innovatory footsteps of biblical philologists such as Gianozzo Manetti, Lorenzo Valla and Desiderius Erasmus in order to reaffirm and concretize the Lutheran principle of the intelligibility of Scripture based on its strictly immanent, that is to say grammatical, investigation. Consequently, I would like to discuss the Clavis Sacrae Scripturae as the confessional yet deliberate outcome of the grammatical and rhetorical curriculum of studia humanitatis. All of this, however, will not lead to the conclusion that the Clavis should still remain the enterprise of a less distinguished follower. For decisions made by Flacius regarding the tradition of patristic, medieval, and humanistic exegesis was constantly founded upon the heuristically critical and genuinely hermeneutical principle. Therefore, it is worth asking what this principle was, or more precisely, how can man use philological tools that do not deprive God of his unconditioned sovereignty.